ANALISIS PENGGUNAAN APLIKASI SISTEM INFORMASI DIREKTORAT JENDERAL PAJAK (SIDJP) DAN KINERJA PEGAWAI (STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA SURABAYA GUBENG) - Saputra, Rahadian (Jurnal Mahasiswa Perpajakan, 2014)
The application of SIDJP which is expected to ease the work of employees tax so as to give positive impact on the performance of employees taxes.The purpose of this study was to know and analyzing use application information system directorate general of taxes (SIDJP) who is running current and analyzing performance of employees in Tax Services Office Primary Surabaya Gubeng. This study uses descriptive qualitative approach. Research focus is onthe use of SIDJP applications for officers and employees in the performance of the Tax Services Office Primary Surabaya Gubeng. This study uses data collection techniques such as interviews and documentation. Selected research instruments researchers is interview guides and form of document recording. Researcher used data analysis techniques with a model of Miles and Huberman.The conclusion of this study isuse of application (SIDJP) easy and useful to operate so as to positively impact the performance of the employees but there are weaknesses in the application of SIDJP.The advice recommended isimprove the capacity of SIDJP application, to add the server, bandwidth and improve connectionsand the addition of application SIDJP feature to account representative (AR) in monitoring taxpayers and features to bailiff requisitioning in helping billing process. Keywords: use application (SIDJP), performance of employees